2018
DOI: 10.1016/j.egypro.2018.08.100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of piston shape and injector geometry on combustion and emission characteristics of syngas in direct-injection spark-ignition engine

Abstract: District heating networks are commonly addressed in the literature as one of the most effective solutions for decreasing the greenhouse gas emissions from the building sector. These systems require high investments which are returned through the heat sales. Due to the changed climate conditions and building renovation policies, heat demand in the future could decrease, prolonging the investment return period. The main scope of this paper is to assess the feasibility of using the heat demand -outdoor temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Due to the axisymmetric structure, half of the engine geometry was taken out for the study in order to reduce the computational effort, as shown in Figure 1. According to Zanforlin and Boretti, 44 Fiore et al, 45 such a modeling approach is acceptable. The fuel injector (six holes) was installed adjacent to the spark plug and injected the fuel after the exhaust valve closing and during the intake stroke.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Due to the axisymmetric structure, half of the engine geometry was taken out for the study in order to reduce the computational effort, as shown in Figure 1. According to Zanforlin and Boretti, 44 Fiore et al, 45 such a modeling approach is acceptable. The fuel injector (six holes) was installed adjacent to the spark plug and injected the fuel after the exhaust valve closing and during the intake stroke.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In this context, hydrogen and syngas represent alternative fuels to conventional fossil fuels, with an increasingly important role in the development of highly efficient and low-emission propulsion and energy production systems, such as Internal Combustion Engines (ICEs) or gas turbines [3][4][5][6][7][8]. Syngas is mainly composed of 𝐶𝐶𝐶𝐶 and 𝐻𝐻 2 , but its composition depends significantly on both the source and the gasification process.…”
Section: Introductionmentioning
confidence: 99%
“…Even though fast combustion of syngas suggested late injection for a better combustion, performance and emission, the lower calorific value resulted in operational limitation for the direct injection system particularly at a higher speed maintaining the air–fuel ratio close to stoichiometry. Fiore et al 23 studied the influence of piston shape and injector geometry on the combustion and emission characteristics of spark ignition engine fueled by syngas (50% by volume of hydrogen, 50% by volume of carbon monoxide) under low/medium load conditions. The result showed that the Omega Combustion Cup (OCC) piston shape was certainly the best choice in order to optimize the combustion process and performance, even if it may lead to a higher nitrogen oxide emission.…”
Section: Introductionmentioning
confidence: 99%